Aplicações da formação de classes de equivalência na intervenção analítico-comportamental ao autismo - SILVA, Álvaro Júnior Melo e (Universidade Federal do Pará, 2018)
The applied potential of the current knowledge on equivalence class formation has much to be explored. There are few studies reported in the literature involving, for example, equivalence of stimuli applied to autism. In this thesis, in addition to the application of stimulus equivalence technology, there is the search for approximation of two areas of study, equivalence of stimuli and verbal behavior, which, in different ways, have approached the phenomenon commonly called language. In the two studies here presented it was investigated the contribution of the equivalence stimulus for the emergence of intraverbal relations in children diagnosed with Autism Spectrum Disorder (ASD). Study 1 evaluated the emergence of intraverbal relations via equivalence-based instruction. Two children with ASD participated in the study. After the teaching of listener relations (AB) and tact (BC), the emergence of intraverbal relations (AC and CA) was verified. The data show that participant Lucia presented the immediate emergency of AC intraverbal relations and the other participant, Lucas, presented low accuracy of performance in the first session and maximum precision in the second session. Lucas’ performance pattern may be considered compatible with delayed emergence of intraverbal relations consistent with the equivalence class formation. At the same time, such data allowed us to question whether or not the observed performance was a result of rapid acquisition of the intraverbal relations due to the prompt provided during the test/training. Study 2 explored this issue, evaluating the acquisition of consistent and inconsistent intraverbal relations with equivalence class formation. The two children of the Study 1 participated in Study 2. After teaching of listener relations (A1B1, A2B2, A3B3, and A4B4) and tact (B1C1, B2C2, B3C3, and B4C4), participants were exposed to consistent intraverbal relations (A1C1, A2C2, C1A1, and C2A2) and inconsistent (A3C4, A4C3, C4A3, and C3A4) with formation of equivalence class formation. The data showed that there was only the acquisition of the consistent relations with class formation for the participant Lucia. For Lucas there was no difference in the acquisition of both types of relations in AC training and there was a slight difference in the acquisition of AC relations, so that consistent intraverbal relations with class formation were learned in fewer sessions or attempts. From Lucia's data, mainly, it can be concluded that an earlier history involving the stimuli of a current relation to be trained facilitates the acquisition of this case the previous contingencies have favored the relation between the stimuli as members of a set or class. Lucas’ data also confirm the initial assumption on the possibility of fast acquisition during test with programmed reinforcement and corrective prompting. The data obtained in this thesis not only prove the applicability of the equivalence of stimuli, but also can encourage new research to use stimulus equivalence as a behavioral technology.